Do nimble hands make for nimble lexicons? Fine motor skills predict knowledge of embodied vocabulary items. Issue 3 (June 2014) - Suggate, Sebastian P.; Stoeger, Heidrun
Theories and research in embodied cognition postulate that cognition grounded in action enjoys a processing advantage. Extending this theory to the study of how fine motor skills (FMS) link to vocabulary development in preschool children, the authors investigated FMS and vocabulary in 76 preschoolers. Building on previous research, they hypothesized that links between FMS and vocabulary were driven by lexical items containing a greater body–object interaction (BOI). After controlling for age and part of speech (i.e., nouns vs. verbs), results indicated that FMS explained a similar amount of variance in BOI vocabulary as general vocabulary did. Mediation analyses indicated that the relation between FMS and general vocabulary was mediated by BOI vocabulary. To the authors' knowledge, this study provides the first evidence that FMS play a role in BOI vocabulary development in the preschool period.